Nutritional intervention during radiotherapy of head and neck cancers - Solecka, Małgorzata; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2018)
Radiotherapy is one of the main forms of treatment for head and neck cancer. This procedure is associated with high toxicity in the irradiated area resulting in patients’ numerous complaints about: inflammation of oral mucous membranes, difficulties with food chewing and swallowing, dry mouth, or impaired taste and smell. Some of these pathologies are temporary and go away at a specific time after treatment, but some of the damage is permanent and irreversible. Complications at the level of the upper gastrointestinal tract cause considerable difficulties in food intake; therefore, intensive dietary counselling is recommended along with nutritional intervention in this group of patients. Adopted and recommended methods of nutritional support during radiotherapy include: modification of the basic diet in terms of consistency, oral nutritional supplements, enteral nutrition with the use of probes, and nutrient gastrostomy.